2022
DOI: 10.5194/isprs-archives-xliii-b4-2022-39-2022
|View full text |Cite
|
Sign up to set email alerts
|

IFCALIGNMENT FOR RASTER-TO-VECTOR GIS RAILWAY CENTRELINE: A CASE STUDY IN THE SOUTH OF ITALY

Abstract: Abstract. Built environment Asset Management (AM) is evolving and renewing itself through the development of new technologies. Building Information Modelling (BIM) is the main methodology for the digitisation process of existing data and information. Although BIM was originally intended for buildings, in the last few years Infrastructure Building Information Modelling (I-BIM) and Civil Information Modelling (CIM) are emerging to manage civil infrastructure. The interaction of infrastructure with the surroundin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Optimization of design in railway construction using BIM is also addressed in other works [32,[45][46][47][48][49][50]. Test of the possibilities and capabilities of storing GIS data in the open standard Industry Foundation Classes (IFC) for BIM was solved in [51]. The study [52] analyses the requirements specified in the Deutsche Bahn AG guidelines for the technical design of railway structures and investigates the feasibility of implementing these rules in a BIM model.…”
Section: Bim In Railway Transportmentioning
confidence: 99%
“…Optimization of design in railway construction using BIM is also addressed in other works [32,[45][46][47][48][49][50]. Test of the possibilities and capabilities of storing GIS data in the open standard Industry Foundation Classes (IFC) for BIM was solved in [51]. The study [52] analyses the requirements specified in the Deutsche Bahn AG guidelines for the technical design of railway structures and investigates the feasibility of implementing these rules in a BIM model.…”
Section: Bim In Railway Transportmentioning
confidence: 99%
“…Similarly, Rogage and Greenwood [7] tried to automate the data transfer from the design and build stage to the FM stage and found that even when a full IFC standard was used, human error in object classification and incompleteness of data meant that the process could not be fully automated. However, despite potential human limitations, some evidence for the effectiveness of updating the IFC schema (and consequently other standardised exchange formats) is given by Garramone and Scaioni [69], who used the 'IFCalignment' entity, a new feature of IFC 4.3, to successfully export GIS raster data, a functionality not previously possible. Similarly, Ciccone et al [62] created a federated model of a railway using infrastructure categories introduced in IFC 4.2 and state that its update is key to interoperability and functionality of models.…”
mentioning
confidence: 99%